CeO2-modified CaO/Ca12Al14O33 bi-functional material for CO2 capture and H2 production in sorption-enhanced steam gasification of biomass. (1st February 2020) - Yan, Xianyao; Li, Yingjie; Ma, Xiaotong; Bian, Zhiguo; Zhao, Jianli; Wang, Zeyan
Abstract: A novel CeO2 -modified CaO/Ca12 Al14 O33 bi-functional material fabricated by wet-mixing method was used in sorption-enhanced steam gasification of biomass for H2 production. The CO2 capture performance of the bi-functional material was investigated during the multiple carbonation/calcination cycles in a dual fixed-bed reactor. H2 production from the sorption-enhanced steam gasification of bagasse char using CeO2 -modified CaO/Ca12 Al14 O33 was studied. When the mass ratio of CaO/Ca12 Al14 O33 /CeO2 is 75:10:15, CO2 capture capacity of CeO2 -modified CaO/Ca12 Al14 O33 reaches 0.48 g/g after 20 cycles under the realistic calcination condition, which is 30% higher than that of CaO/Ca12 Al14 O33 . The average H2 concentration and yield using CeO2 -modified CaO/Ca12 Al14 O33 during 10 cycles achieve 81.1 vol% and 0.124 L/g, which are 17.4% and 47.3% higher than those using CaO/Ca12 Al14 O33, respectively. CeO2 in CeO2 -modified CaO/Ca12 Al14 O33 enhances water gas shift and steam methane reforming reactions. CeO2 -modified CaO/Ca12 Al14 O33 possesses stronger basicity, and Ce 3+ in the surface creates oxygen vacancies and promotes the conductivity of lattice oxygen, which are favorable for CO2 capture. CeO2 improves the cyclic stability of CaO/Ca12 Al14 O33 and stabilizes pores in 10–100 nm in diameter, which facilitates CO2 capture and H2 production. Thus, CeO2 -modified CaO/Ca12 Al14 O33 appears promising for H2 production from the sorption-enhanced steam gasification of biomass. Highlights: CeO2 -modified CaO/Ca12 Al14 O33 bi-functional material is good in biomass gasification. CeO2 -modified CaO/Ca12 Al14 O33 possesses high cyclic CO2 capture capacity. CeO2 -modified CaO/Ca12 Al14 O33 favors H2 production in steam gasification of biomass. CeO2 -modified CaO/Ca12 Al14 O33 obtains strong basicity due to the presence of CeO2 . CeO2 -modified CaO/Ca12 Al14 O33 maintains stable porous structure in cycles.